BIOSORPTION OF Ni (II) IONS BY ARABICAN COFFEE FRUIT (Coffea arabica) - Serly Tandigau; Nursiah La Nafie; Prastawa Budi (Hasanuddin University, 2018)
Arabica coffee fruit peel is a material that is abundant and cheap. The material has been used as an adsorbent in the biosorption process for the removal of metal ions of Ni(II) from wastewater. Biosorption of Ni(II) ion by dragon fruit peel was done on the variation of particle size, variation of contact time, pH and concentration. Adsorption capacity was studied by both isotherm adsorptions of Langmuir and Freundlich. The concentration of metal ions Ni(II) before and after adsorption was determined using Atomic Absorption Spectrophotometer (AAS). Results showed that the optimum time was 50 minutes and the optimum pH was 6 with 120 mesh of particle size of biosorption. Results showed that the biosorption of Ni(II) ion using Arabica coffee fruit peel fullfilled the isotherm Langmuir model with the biosorption capacity (Qo) of 18.86 mg/g. The functional group involved in metal ion biosorption of Ni(II) by the peel of coffee fruit is a hydroxyl group (-OH).